ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN PADA SSC (SITUBONDO SPORT CENTER) DI SITUBONDO DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Salam, Nadira Annisa Nur; Arief, Mohammad Yahya; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Marketing management can also be defined as the art and science of selecting target markets designed to create, build and maintain profitable exchanges to achieve company goals, for this reason, proper marketing management can increase, especially ini the development of SSC (Situbondo Sport Center). The purpose of this study was to analyze and test the effect of Physical evidence and Service excellence in determining customer loyalty with customer satisfaction as an intervening variable. The population in the study was SSC (Situbondo Sport Center) customers. The sampling method was determined by nonprobability sampling with purposive sampling. Data analysis and hypothesis testing in research using the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application, show that Physical evidence has a significant positive effect on customer satisfaction, Service excellence has a significant positive effect on customer satisfaction, Physical evidence has a negative but insignificant effect on customer loyalty, Service excellence has a significant positive effect on customer loyalty, Customer satisfaction has a significant positive effect on customer loyalty. The results of the indirect effect hypothesis show that the Physical evidence variable has a significant positive effect on customer loyalty through customer satisfaction, the service excellence variable has a significant positive effect on customer loyalty through customer satisfaction.